Integrating Social Media as a Communication Tool in STEM Education: Infographics of the UNJ Digital Library System - Ervina, Ervina; Shylvia, Ita; Fauzi, M. Reza (Current STEAM and Education Research, 2025)
The purpose of this study is to produce an Instagram infographic account of the Jakarta State University (UNJ) library, which can be used as a personal or public reference to find out library-related information. The method used in this research is research and development by adopting the 4D model approach, which is carried out from the first step to the fourth step including Define, Design, Develop, and Disseminate. The UNJ's infographic library Instagram account contains library information content including the number of library visitors, number of book borrowers, number of library collections, e-journal and e-book services, number of library members, and total collections of scientific works, thesis, and references. The development of the Instagram infographic account is validated by a design expert.